Sighting history and observations of southern right whales following satellite tagging off South Africa - Best, Peter B.; Mate, Bruce (J. Cetacean Res. Manage., 2023)
In September 2001, satellite tags were deployed on 21 southern right whales (Eubalaena australis) in South African coastal waters, including eight cows accompanied by newborn calves. To date there have been 26 re-sightings of 11 of these individuals (or their calves) at intervals of 27-1,502 days. So far, 85.7% of the females with calves have been re-sighted with a second calf, at intervals comparable to those that the same individuals showed before tagging. All tags seem to have been shed between 27 and 36 months of tagging. Superficial and remote examination of wound sites indicated the frequent formation of divots with accompanying scarring and cyamids, but little sign of localised (and none of regional) swelling.